The use of viruses in anti-cancer therapies - new achievements and challenges - Małgorzata Grudnik; Katarzyna Grudnik; Maciej Słomian; Monika Prokurat; Karolina Lau; Katarzyna Kryszczyszyn-Musialik (Śląski Uniwersytet Medyczny w Katowicach, 2024)
Viruses are gaining pivotal significance in innovative therapeutic strategies, underscoring their growing role in the field of oncology. The utilization of oncolytic viruses for the selective recognition and effective elimination of cancerous cells has captured the interest of scientists for many years. Due to the unique features of their application, such as greater patient comfort compared to the use of conventional therapies alone, a positive response of the body to treatment, and improved patient survival rates, virus-based therapies may become a pivotal pillar of modern oncology in future, particularly when integrated into combination therapies. It is assumed that further research into the specifics of viruses and their interactions will enable the development of more precise and effective immunotherapies targeted at cancers. However, considering the dynamic nature of these strategies, simultaneous rigorous monitoring of the potential hazards associated with virus application is imperative to ensure patient safety and further advancements in oncology. This review focuses on the analysis of virus application in cancer therapy and the emerging challenges related to clinical studies, placing particular emphasis on their specificity, versatility, and the direction in which modern forms of therapy are heading.